Inclusion of Mental Health in National Rural Health Mission (NRHM): Challenges and Prospects - Mudasir Rajab; Mohd Azam Khan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Health, according to the World Health Organization, is “a state of complete physical, mental and social well-being and not merely the absence of disease and infirmity”. Over time, different definitions have been given for various objectives. Healthy behaviors may be motivated, like regular exercise and getting sufficient sleep, while unhealthy behaviors, like smoking or more stress, can be reduced or ignored. Some variables that impact health are caused by individual decisions, such as whether for busy in high-risk activities, while others are the result of structural factors, such as how society is structured and how easy or difficult it is for individuals to get primary healthcare services. Others, including hereditary illnesses, are independent of individual and societal preferences. The National Rural Health Mission (NRHM) was introduced by the Indian government on April 12th, 2005. The mission's objective is to increase peoples' access to and availability of high-quality healthcare, particularly for those living in rural regions, the underprivileged, disabled, women, and children. To address the mental health issues and challenges, it must be the part of NRHM. In this paper the objective is to analyses the importance of inclusion of mental health in NRHM and to examine the role of National Mental Health Program (NMHP) and District Mental Health Program (DMHP) since its inception.